2013
DOI: 10.1016/j.cyto.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory intestinal damage induced by 5-fluorouracil requires IL-4

Abstract: Our data suggest that IL-4 participates as a pro-inflammatory cytokine in a 5-FU-induced intestinal damage model and suggests that IL-4 antagonists may be novel therapeutics for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 14 publications
8
55
1
Order By: Relevance
“…Neutrophil infiltration has been reported in several studies that assessed mucositis (24,32,33). We observed intermediate MPO activity in animals receiving L-arginine.…”
Section: Discussionsupporting
confidence: 46%
“…Neutrophil infiltration has been reported in several studies that assessed mucositis (24,32,33). We observed intermediate MPO activity in animals receiving L-arginine.…”
Section: Discussionsupporting
confidence: 46%
“…In addition, other factors, such as the use of some medications, can also contribute to the breakdown of this immunological tolerance against commensals. It has been reported that chemotherapeutic agents, such as 5-fluoracil, that are widely used in the treatment of advanced solid tumors, may also lead to the development of another inflammatory condition of the GIT known as mucositis, a disease characterized by painful inflammation and ulceration of the mucosal membranes (Soares et al, 2013; Pedroso et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As observed in treated patients, 5-FU shows a high toxicity in gastrointestinal tract, inducing intestinal damage such as intestinal mucositis [34]. Previous studies have established the where R 1 is a C 1 -C 6 straight chain alkyl substituted with deuterium or (C 1 -C 5 straight chain alkylene)-COOR 2 wherein the straight chain alkylene is substituted with deuterium; and R 2 is selected from hydrogen, (C 1 -C 6 ) alkyl, (C 5 -C 14 ) aryl, (C 6 -C 16 ) arylalkyl, 5 --14 membered heteroaryl and 6 --16 membered heteroarylalkyl, wherein when R 2 is other than hydrogen, R 2 is optionally substituted with deuterium.…”
Section: -Fu Derivativesmentioning
confidence: 97%